2016
DOI: 10.1002/2016jf003921
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological and geochemistry changes in permafrost after the 2002 tundra wildfire in Kougarok, Seward Peninsula, Alaska

Abstract: Geomorphological and thermohydrological changes to tundra, caused by a wildfire in 2002 on the central Seward Peninsula of Alaska, were investigated as a case study for understanding the response from ice‐rich permafrost terrain to surface disturbance. Frozen and unfrozen soil samples were collected at burned and unburned areas, and then water isotope geochemistry and cryostratigraphy of the active layer and near‐surface permafrost were analyzed to investigate past hydrological and freeze/thaw conditions and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…1). The field investigations confirmed that the landscape was broadly homogenous in any slope direction (Iwahana et al 2016) if fires did not occur for long term (Narita et al 2015).…”
Section: Study Area and Field Methodsmentioning
confidence: 72%
See 3 more Smart Citations
“…1). The field investigations confirmed that the landscape was broadly homogenous in any slope direction (Iwahana et al 2016) if fires did not occur for long term (Narita et al 2015).…”
Section: Study Area and Field Methodsmentioning
confidence: 72%
“…These reports suggest that fire affects vegetation structures at various spatio-temporal scales. Satellite imagery confirms that thermokarsts occur frequently in the burned areas of Kougarok where polygonal networks of high-centered polygon derived by melting ice wedges are well developed (Iwahana et al 2016). However, no subsidence was observed in adjacent unburned sites.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Fire frequency and severity in the Arctic are expected to increase in the future and can have large-scale and long-lasting effects on hydrological and biogeochemical cycling (Flannigan et al, 2005;Hu et al, 2015). For instance, fire can change the landscape locally by enhancing erosion and thermokarst development (Chipman & Hu, 2017;Iwahana et al, 2016;Jones et al, 2015), and can have global impacts by releasing soil carbon that contributes to global climate change (Abbott et al, 2016;Balshi et al, 2007;Schuur et al, 2015). In continuous permafrost settings, these changes are primarily driven by increases in the thickness of the active layer (the soil above the permafrost which thaws and refreezes annually) following fire.…”
Section: Introductionmentioning
confidence: 99%